Pembaharuan Pendidikan Islam (Pesantren, Madrasah, & Sekolah “Elit” Islam) - Hilman Rizky Hasibuan; Yuda Ismail Lubis; Sehat Sultoni Dalimunthe (Journal on Education, 2023)
Responding to the ever-evolving era requires various efforts to improve structures in various fields, be it political, social or educational institutions, that's why every era there is educational renewal, both general education and Islamic education. This study aims to describe the renewal of Islamic education starting from Islamic boarding schools, madrasas until now, which are known as Islamic elite schools. This research uses literature study method. The results of this study conclude that the renewal of Islamic education starts from Islamic boarding schools, madrasas and elite schools based on the demands of the times to be able to excel in various scientific fields, not only in the field of Islamic sciences but this renewal also aims for Islamic educational institutions to excel in general scientific fields.